2016
DOI: 10.1080/10255842.2016.1247833
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow in the cerebral venous system: modeling and simulation

Abstract: The development of a software platform incorporating all aspects, from medical imaging data, through three-dimensional reconstruction and suitable meshing, up to simulation of blood flow in patient-specific geometries, is a crucial challenge in biomedical engineering. In the present study, a fully three-dimensional blood flow simulation is carried out through a complete rigid macrovascular circuit, namely the intracranial venous network, instead of a reduced order simulation and partial vascular network. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Note that an asymmetric behavior of the venous ow appears, equally showed in [27], that could be explained, at least partly, by the asymmetric architecture of the venous network. Finally, to give an insight about the importance of the preconditioning strategy when solving complex ow problems, we gather in Table 3 results allowing a direct comparison between three possible choices in term of .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that an asymmetric behavior of the venous ow appears, equally showed in [27], that could be explained, at least partly, by the asymmetric architecture of the venous network. Finally, to give an insight about the importance of the preconditioning strategy when solving complex ow problems, we gather in Table 3 results allowing a direct comparison between three possible choices in term of .…”
mentioning
confidence: 99%
“…A computational model based on the assumptions that at this scale blood can be considered as an incompressible, homogeneous, Newtonian uid, leads to the description of the ow by means of the Navier-Stokes equations [27] in a xed domain. Body forces contribution (for instance gravity), can be incorporated in the model through the right-hand side term and walls are assumed to be rigid.…”
mentioning
confidence: 99%
“…According to previous studies, the IQQA software can be used to reconstruct the spatial structure of the blood vessels precisely, and the FLUENT software can be used to simulate the blood flow in vessels accurately 19–25. Moreover, it has been reported that Navier-Stokes equations can be used to compute the haemodynamics of the cerebral arterial and venous system 26 27. Since the inner diameters of the inferior vena cava, the hepatic veins, the portal vein and its main branches are much larger than the diameters of red blood cells, and the blood flow is relatively steady and fast in these big vessels, the whole blood can be assumed to be an incompressible Newtonian fluid, and thus the blood flow can also be modelled by the Navier-Stokes equations 28 29.…”
Section: Discussionmentioning
confidence: 99%
“…Note that there is another force, Saffman force, which is channel center/wall-directed lift force experienced by particles lagging/leading the fluid and it is not shown in the figure to avoid confusions. Qualitatively, in most of the literature, that relied on passive techniques, and in a fair amount of the literature, focused on active approaches, the numerical simulation had been used to refine the Qualitatively, in most of the literature, that relied on passive techniques, and in a fair amount of the literature, focused on active approaches, the numerical simulation had been used to refine the understanding of physical phenomena, or/and optimize micro-channel geometrical aspects [41][42][43][44][45][46][47][48][49]. It is noteworthy that herein, we focus mostly on separating and trapping techniques on mammalian cells that are passive and suspended inflow.…”
Section: Microfluidic Systems For Cellular Flow Manipulationmentioning
confidence: 99%
“…understanding of physical phenomena, or/and optimize micro-channel geometrical aspects [41][42][43][44][45][46][47][48][49]. It is noteworthy that herein, we focus mostly on separating and trapping techniques on mammalian cells that are passive and suspended inflow.…”
Section: Appl Sci 2019 9 X For Peer Review 3 Of 23mentioning
confidence: 99%